Improving mental health among people living with HIV: a review of intervention trials in low- and middle-income countries - K. J. Sikkema; A. C. Dennis; M. H. Watt; K. W. Choi; T. T. Yemeke; J. A. Joska (Cambridge Prisms: Global Mental Health, 2015)
People living with HIV (PLWH) experience greater psychological distress than the general population. Evidence from high-incomes countries suggests that psychological interventions for PLWH can improve mental health symptoms, quality of life, and HIV care engagement. However, little is known about the effectiveness of mental health interventions for PLWH in low- and middle-income countries (LMICs), where the large majority of PLWH reside. This systematized review aims to synthesize findings from mental health intervention trials with PLWH in LMICs to inform the delivery of mental health services in these settings. A systematic search strategy was undertaken to identify peer-reviewed published papers of intervention trials addressing negative psychological states or disorders (e.g. depression, anxiety) among PLWH in LMIC settings. Search results were assessed against pre-established inclusion and exclusion criteria. Data from papers meeting criteria were extracted for synthesis. Twenty-six papers, published between 2000 and 2014, describing 22 unique interventions were identified. Trials were implemented in sub-Saharan Africa (n = 13), Asia (n = 7), and the Middle East (n = 2), and addressed mental health using a variety of approaches, including cognitive-behavioral (n = 18), family-level (n = 2), and pharmacological (n = 2) treatments. Four randomized controlled trials reported significant intervention effects in mental health outcomes, and 11 preliminary studies demonstrated promising findings. Among the limited mental health intervention trials with PLWH in LMICs, few demonstrated efficacy. Mental health interventions for PLWH in LMICs must be further developed and adapted for resource-limited settings to improve effectiveness.